Study of the influence of temperature on the measurement accuracy of transit-time ultrasonic flowmeters. Issue 2 (1st October 2018) - Ge, Liang; Deng, Hongxia; Wang, Qing; Hu, Ze; Li, Junlan
Abstract : Purpose: The purpose of this study is to deal largely with the influence of temperature variation on the measurement accuracy of transit-time ultrasonic flowmeter. Design/methodology/approach: The causes of measurement error due to temperature are qualitatively and quantitatively analyzed, and a mathematical model is established. The experimental data are processed and analyzed, and the temperature compensation coefficient of flow measurement is obtained. Findings: The experimental results show that the flow measurement results by temperature compensation are helpful in improving the measurement accuracy of the ultrasonic flowmeter. Practical implications: This study has certain application value, which can provide theoretical support for the design of high-precision ultrasonic flowmeters and design guidance. Originality/value: It is worth emphasizing that there are few research studies on the influence factors of temperature. This paper focuses on the influence of the temperature change on the flowmeter that is modeled, and the high precision flow parameter test system is designed based on the established model.